2016
DOI: 10.1097/ico.0000000000000922
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Alterations in Chronic Renal Failure

Abstract: Corneal endothelial alteration is present in patients with chronic renal failure, more marked in patients undergoing hemodialysis and with raised blood urea level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…[2][3][4] Beyond the deterioration of renal capillary endothelium, diminished endothelial repair systems and decreased number of endothelial progenitor cells were also reported in DM by previous studies. 4,5 Consequently, microalbuminuria is accepted as a critical marker of generalised endothelial dysfunction, which is involved in pathogenesis of many systemic conditions such as heart disease, stroke, venous thrombosis, tumour growth, metastasis and various infections. [4][5][6] However, it is not clear whether corneal endothelium is also affected by similar pathological mechanisms in patients with microalbuminuria.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…[2][3][4] Beyond the deterioration of renal capillary endothelium, diminished endothelial repair systems and decreased number of endothelial progenitor cells were also reported in DM by previous studies. 4,5 Consequently, microalbuminuria is accepted as a critical marker of generalised endothelial dysfunction, which is involved in pathogenesis of many systemic conditions such as heart disease, stroke, venous thrombosis, tumour growth, metastasis and various infections. [4][5][6] However, it is not clear whether corneal endothelium is also affected by similar pathological mechanisms in patients with microalbuminuria.…”
mentioning
confidence: 56%
“…1,2 In DM, hyperglycaemia-induced various mediators (inflammatory cytokines, advanced glycation end products, reactive oxygen species and vascular endothelial growth factor) trigger renal capillary endothelial damage that result in glomerular hyperfiltration and microalbuminuria. [1][2][3][4] Capillary rarefaction, glomerular fibrosis and renal failure are the major findings of end-stage diabetic nephropathy. [2][3][4] Beyond the deterioration of renal capillary endothelium, diminished endothelial repair systems and decreased number of endothelial progenitor cells were also reported in DM by previous studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic hemodynamic parameters, as well as eye fluid volume and composition, can change with HD. There are many studies examining the anterior and posterior segment showed significant changes in IOP and CCT (8)(9)(10)(11)(12). Given the contradictory reports of HD affecting IOP, precise and mechanistic insights of HD on IOP are not well-established (11,13,14).…”
Section: Introductionmentioning
confidence: 99%